Psychometric properties of the Spanish version of the Flourishing Scale in the Honduran population - Landa-Blanco, Miguel; Cortés-Ramos, Antonio; Vásquez, Gabriela; Reyes, Yarell; Echenique, Yarani (Frontiers in Psychology, 2023)
Studying Flourishing is important to understand wellbeing. The current study aimed to determine the psychometric properties of the Spanish version of the Flourishing Scale (FS) in the Honduran population. The primary sample consisted of 422 residents of the Central District of Honduras; this included 275 (65.17%) women and 147 men (34.83%). Their average age was 28.18 years (SD=10.58). Findings from the Exploratory Factor Analysis and Confirmatory Factor Analysis support a unidimensional factor structure. The FS achieved a high internal consistency with McDonald's ω=0.89, 95% CI [0.86, 0.91]. The average inter-item correlation was 0.48, 95% CI [0.43, 0.53]. Using Student's t-test for paired samples, results indicate that none of the FS items varied significantly between baseline and post-test. Additionally, Spearman's rho was used to correlate test-retest scores; this yielded a statistically significant correlation coefficient of 0.66. The Flourishing Scale had adequate convergent validity with the Subjective Happiness Scale (r=0.70) and the PANAS-Positive Affect Subscale (r=0.70). (p<.001). In contrast, it correlates inversely with the PANAS-Negative Affect Subscale (r=-0.34) and the PHQ-9 (r=-0.51). Strict measurement invariance for sex was supported. The results indicate that the Flourishing Scale has robust psychometric properties for the Honduran population. Practical implications for public policy are discussed.